2017
DOI: 10.1002/stem.2758
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: The Cellular Conspiracy of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is incurable and devastating. A dearth of therapies has galvanized experimental focus onto the cellular and molecular mechanisms that both initiate and subsequently drive motor neuron degeneration. A traditional view of ALS pathogenesis posits that disease-specific injury to a subtype of neurons is mechanistically cell-autonomous. This "neuron-centric" view has biased past research efforts. However, a wealth of accumulating evidence now strongly implicates non-neuronal cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 118 publications
(138 reference statements)
0
31
0
1
Order By: Relevance
“…A number of possible pathways of disease have been described, including mitochondrial dysfunction, glutamate excitotoxicity (26,27), problems with autophagy (28) and altered RNA metabolism (29). Furthermore, the death of motor neurons can be "non-cell autonomous, " meaning that other types of cells such as astrocytes, microglia and possibly oligodendrocytes can drive motor neuron death (30,31). There has been considerable research on the type of cell death that occurs in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…A number of possible pathways of disease have been described, including mitochondrial dysfunction, glutamate excitotoxicity (26,27), problems with autophagy (28) and altered RNA metabolism (29). Furthermore, the death of motor neurons can be "non-cell autonomous, " meaning that other types of cells such as astrocytes, microglia and possibly oligodendrocytes can drive motor neuron death (30,31). There has been considerable research on the type of cell death that occurs in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the white matter (WM) structure have been reported to be more pronounced compared with those in MN structures [3] and have been described also in the perforant path area of ALS patients [4], likely contributing to typical ALS symptoms which include motor and neurological deficits and cognitive decline. Globally, these observations have laid the foundation to consider ALS as a non-cell autonomous disease [5]. Accordingly, a growing amount of evidence has shown that mutant SOD1 expression in non-neuronal cells, mainly astrocytes and microglia, has deleterious effects that contribute to neuronal death [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the gene coding for Cu/Zn Superoxide Dismutase 1 (SOD1) constitute around 20% of familial ALS (Chen, Sayana, Zhang, & Le, ; Rosen et al., ). Although defined as motor neuron‐specific disorder, ALS pathogenesis involves non‐neuronal cells, too (Serio & Patani, ). A characteristic feature of neurodegenerative conditions is the concomitant occurrence of neuroinflammation, which is typically characterized by activation of microglia and infiltration of peripheral lymphocytes and macrophages (Liu & Wang, ).…”
Section: Introductionmentioning
confidence: 99%